Early Experience of Spinal Instrumentation at NITOR, Dhaka "Spinal Stabilization is the Goal for Early Mobilization" (Bangladesh Medical Journal, 2009)
In our country spinal injury patients are mostly treated conservatively for 12 to 18 weeks. So complications of immobilization for long time are more (bed sore, UTI, respiratory infection, paralytic ilius, wt. loss and lastly psychological distress).With this in our mind spinal stabilization was done for early mobilization of the paraplegic patients to prevent complications of immobilization. Objective of this study were: to reduce pain, to early mobilize for prevention of complications of immobilization and to assess the improvement after spinal stabilization. This Randomized prospective study was conducted from May 2003 to January 2004 at Tertiary referral Orthopaedic Institute.   DOI: 10.3329/bmj.v38i1.3581 Bangladesh Medical Journal 38(1) 2009 15-17